Analysis Of Factors Affecting Students' Interest In Learning Natural Sciences In Grade III Of SD Negeri 1 Bayan - Hanaria, Baiq Rika; Hadi, Rusman; Habiburrahman, H. Lalu (Peneliti.net, 2025)
Interest is a consistent tendency to pay attention to and be involved in certain activities that a person is drawn to. Interest has a significant influence on learning activities, especially in IPAS learning. The IPAS learning process at SDN 1 Bayan has not been running smoothly due to students’ lack of interest in participating in IPAS lessons. The purpose of this study is to describe the level of students’ learning interest and the factors that influence their interest in IPAS learning. This research was conducted at SDN 1 Bayan. The subjects in this study were the classroom teacher who teaches IPAS and the third-grade students. This research is a qualitative descriptive study. Data collection techniques used were interviews, observation, and documentation. The research results show that the factors influencing the learning interest of third-grade students at SDN 1 Bayan in IPAS learning include the distance between home and school being quite far, limited student pocket money, lack of parental attention to their children’s school needs, children experiencing broken homes, lack of parental affection, some students living with their grandparents—these are some of the reasons for the low learning interest, causing students to feel lazy during study, especially in IPAS lessons. Furthermore, the learning method often used is lecturing, and during the learning process, students tend to sit at the back because they feel bored. The way the teacher analyzes students’ learning difficulties in IPAS learning is by inviting struggling students to engage in discussions. This kind of encouragement plays an important role in fostering children's interest. This research is expected to serve as input for IPAS teachers in particular, and subject teachers in general, in overcoming students’ learning difficulties.